Diuretic and hipotensive activity of aqueous extract of parsley seeds (Petroselinum sativum Hoffm.) in rats - De Campos, Kleber Eduardo [UNESP]; Balbi, Ana Paula Coelho; Alves, Maria José Queiroz De Freita [UNESP] (Springer Nature, 2009)
Purpose: the vegetal specie, Petroselinum sativum Hoff., known as parsley, is widely used in the Brazilian folk medicine as diuretic. The objective of this study is to verify if Brazilian use of parsley aqueous extract has similar effects with investigations that show a diuretic effect of P. sativum in rats. Methods: 19 rats were anesthetized and we cannulated the trachea, left carotid artery (for arterial pressure measurement) and urinary bladder (to collect urine). After 40 minutes of adaptive surgery conditions, anesthetized rats were administrated as related with their group: control (CON), oral administration with 1.0 mL of filtered water, and treated group (AE), oral administration with aqueous extract of seeds of parsley 20% (AE). Urine was collected three times (30 minutes each) and then this material was used for sodium and potassium determinations, to evaluate the amount excreted of these ions. Blood pressure was measured by mercury manometer for 9 times. All data were statistically evaluated. Results and conclusion: in the analyzed parameters, CON group did not show any differences; but AE group showed an increased of urinary flow and sodium and potassium amount excreted, and also decreased arterial pressure. All the parameters presented these modifications after 30 minutes of administration of AE (p<0.05). These results show that the treatment with the AE results in natriuretic and hypotensive effects in anesthetized Wistar rats, confirming the use of Brazilian population of this herb as diuretic.
Keywords: Diuretic effect; Hypotensive effects; Parsley; Petroselinum sativum; Umbelliferae